KARAP/DAP12/TYROBP: three names and a multiplicity of biological functions in cellular interactions - Vivier, Eric (Henry Stewart Talks, 2012)
KARAP/DAP12/Tyrobp: Three names and a multiplicity of biological functions in cellular interactions, Signal transduction, ITAM, Myeloid cells, Osteoclasts, Bone remodelling, Giant cells formation, Inflammation, Natural killer cells